Playful Lenses: Using Twine to Facilitate Open Social Scholarship through Game-based Inquiry, Research, and Scholarly Communication - Wilson, Rebecca; Saklofske, Jon (KULA, 2019)
In academic contexts, digital games are often studied as texts or are used as pedagogical tools to teach basic concepts in early education situations. Less usefully, their systems and economies are often co-opted and decontextualized in short-sighted attempts to “gamify” various aspects of learning or training. However, given that games are highly controlled, conditional, choice-and-consequence-based, problem-solving environments in which players are expected to interact with simulated settings and elements after agreeing to take on particular roles and subject positions, there are promising potential uses of these experiences in academic contexts that have not been fully considered. Motivated by the imperative to explore alternative modes and methods of scholarly research and communication, and guided by the values of open social scholarship practices, this paper reconsiders games not as things to study, but as instruments to study with. Given that games can function as simulations, models, arguments and creative collaboratories, game-based inquiry can be used as a potential method of post-secondary and post-graduate humanities research and scholarly communication. While these ideas have been explored in a preliminary way in relation to a number of different academic disciplines (Donchin 1995; Boot 2015; Mitgutsch and Weise 2011; Westecott 2011) this paper is meant to catalyse a humanities-calibrated consideration of the pragmatics and potentials of game-based research, games as instances of critical making and scholarly communication, and more complex forms of game-based learning than those currently practiced. A number of examples that make use of the open source Twine platform will be featured.